IgE receptor responsiveness of basophils in chronic inducible urticaria - Mizuno, Mayuko; Oda, Yoshiko; Imamura, Shinya; Washio, Ken; Fukumoto, Takeshi; Fukunaga, Atsushi (Frontiers in Immunology, 2022)
Introduction: Chronic inducible urticaria (CIndU) is a subgroup of chronic urticaria induced by a specific stimulus. We evaluated basophil characteristics in patients with CIndU and compared with those in patients with chronic spontaneous urticaria (CSU) and healthy controls (HCs). Methods: Blood was collected from patients, and a basophil activation test (BAT) was performed. Basophil responsiveness and surface marker expression in patients with CIndU were compared with those in patients with CSU and HCs. For some patients with CIndU, blood was collected before and after wheals were induced. In these cases, we compared the responsiveness of basophils before and after the appearance of wheals. Result: HCs (n=23) and patients with CIndU (n=24) or CSU (n=38) were enrolled in the study. The degree of basophil activation at steady state in patients with CIndU was higher than in HCs. Basophil responsiveness via high-affinity IgE receptor (FcεRI) stimulation with anti-IgE or anti-FcεRI antibody in patients with CIndU was equivalent to that in HCs, and higher than that in patients with CSU. No abnormalities in IgE and FcεRI expressions on the surface of basophils in patients with CIndU were observed. When we induced wheals in some patients with CIndU and performed a BAT before and after the appearance of wheals, no significant changes were found. Conclusion: Peripheral blood basophils in CIndU were slightly activated at steady state, but no abnormalities in basophil responsiveness. In future, a higher number of cases should be enrolled to confirm the role of basophils and refine therapeutic targets for CIndU.